Adverse effects of home remedies for cold influenced by social media. - Niharika; Sakshi, Minocha; Rosaline, Mishra; Praveen Kumar, Gaur (European Journal of Pediatric Dermatology, 2024)
Medicinal plants have numerous positive health effects and social media promotes their use for various diseases. Garlic, a well-known herbaceous species, is often used to treat cough and cold, but it has been linked to adverse side effects, including burns. The purpose of our article is to advise patients not to apply fresh garlic to their skin or mucous membranes without knowing the subsequent consequences. In our study, an 8-month-old little girl was treated for cold and cough by using raw garlic paste on his foot, which resulted in a chemical burn.